2021
DOI: 10.3389/fneur.2021.613441
|View full text |Cite
|
Sign up to set email alerts
|

A Modified in vitro Clot Lysis Assay Predicts Outcomes in Non-traumatic Intracerebral Hemorrhage Stroke Patients—The IRONHEART Study

Abstract: Background: Non-traumatic intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes and results in a higher rate of mortality as compared to ischemic strokes. In the IRONHEART study, we aimed to find out whether a modified in vitro clot lysis assay method, that includes the effect of neutrophil extracellular traps (NETs) might predict ICH outcomes.Patients and Methods: In this prospective, observational study, 89 consecutive non-traumatic ICH patients were enrolled. Exclusion criteria included aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Currently, only on-admission blood glucose levels and INR values were analyzed. Detailed hemostasis, renal function, white blood cells, hemoglobin, hematocrit, and platelet count data were described in our previous article ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only on-admission blood glucose levels and INR values were analyzed. Detailed hemostasis, renal function, white blood cells, hemoglobin, hematocrit, and platelet count data were described in our previous article ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…A conventional in vitro clot lysis assay (CLA) and a modified CLA (mCLA)—including cell-free DNA and histones—were performed from stored platelet-free plasma, taken on admission. Parameters of mCLA correlated with ICH bleeding volume ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several markers, including MPO-DNA, citH3, cfDNA, nucleosomes, DNase-I, and circulating CitH3, have been identified as potential indicators of the level of NETs and can be utilized as biomarkers for predicting ischaemia in peripheral artery disease and coronary artery disease [ 52 , 53 ]. Research has demonstrated that the levels of both neutrophil and NET markers are similarly high in the lysate supernatants of thrombi retrieved after mechanical thrombectomy.…”
Section: The Role Of Nets In Stroke Pathologymentioning
confidence: 99%
“…A recent research reported the NET infiltration in the brain of patients who died from spontaneous intracerebral hemorrhage (sICH), suggesting that NETs might interact with early hemostasis within the hematoma core and with the surrounding neuroinflammatory response (57). Orbań-Kaĺmańdi et al pointed out that a modified clot lysis assay, incorporating the effect of NETs, could suggest unfavorable outcomes in spontaneous, nontraumatic ICH based on a prospective observational study data (58). Also, in subarachnoid hemorrhage (SAH), the current studies revealed that NETs can induce the alteration of microglia into a proinflammation subtype in order to promote neuroinflammation and cause adverse consequences, suggesting that NETs may be a potential target for the treatment SAH in its early phase (59,60).…”
Section: Hemorrhagic Apoplexymentioning
confidence: 99%
“…Orbán-Kálmándi et al. pointed out that a modified clot lysis assay, incorporating the effect of NETs, could suggest unfavorable outcomes in spontaneous, nontraumatic ICH based on a prospective observational study data ( 58 ). Also, in subarachnoid hemorrhage (SAH), the current studies revealed that NETs can induce the alteration of microglia into a proinflammation subtype in order to promote neuroinflammation and cause adverse consequences, suggesting that NETs may be a potential target for the treatment SAH in its early phase ( 59 , 60 ).…”
Section: Hemorrhagic Apoplexymentioning
confidence: 99%